Asuhan Kebidanan Komprehensif pada Ny. L di RSIA Masyita Makassar - Fitriani Fitriani; Nurlina Akbar; Sitti Nurana (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2025)
Comprehensive midwifery care is a continuous approach that includes support for mothers from the time of pregnancy, labor, postpartum period, newborn care, to family planning services. Midwives play a role in providing comprehensive care from pregnancy to family planning to detect early problems, complications, and challenges. This study aims to implement comprehensive midwifery care. The method used refers to the seven-step management of care according to Varney, which is documented through the SOAP format, starting from identifying basic data, identifying actual diagnosis/problems, identifying potential diagnosis/problems, immediate actions/collaboration, midwifery care management, and evaluation, The SOAP documentation consists of subjective and objective data, clinical analysis, and the care interventions provided.. The results of the study were obtained from a patient reviewed Mrs. L, age 36, G5P4A0 at Masyita Hospital in Makassar. pregnancy progressed normally, with four antenatal visits recorded. Labor occurred spontaneously without complications, resulting in the birth of a healthy infant weighing 3700 grams and measuring 50 cm in length, with an upper arm circumference of 11 cm and an APGAR 8/10. The postpartum period was uneventful, and complaints remained within physiological limits. In the family planning phase, the patient received counseling and opted for an implant contraceptive method.